Development of Istima’ Materials Based on the Scientific Approach Using the Audacity Application at SD Islam Cendekia Faiha Palembang - Nur Hidaya; Wasilah; Rendi Sabana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to develop Istima’ (listening) materials based on the Audacity approach at SD Islam Cendekia Faiha Palembang. The method used is Research and Development (R&D), which includes stages of needs analysis, design, development, and limited trials. The results of expert validation in both content and media indicate that the developed materials are highly feasible for use. The use of Audacity facilitates teachers in creating audio materials and enhances student engagement in learning. The resulting Istima’ materials are effective, engaging, and aligned with the characteristics of elementary school students.